Demonology and Terminology in Jubilees Spirits or Demons? - Patmore, Hector M. ca. 20./21. Jh. (2023)
This paper examines the terminology related to demons in Jubilees. It argues that important nuances have been lost in the process of translation. Specifically, it argues that the original Hebrew of Jubilees always used רוחות to refer to demons. It reexamines cases in which the Ethiopic and/or Latin translations would appear to contradict this conclusion (i.e., Jub. 7:27; 10:1–2) in light of textual evidence from the Book of Asaf, the Byzantine chronicler Syncellus, and the Book of Watchers. In the case of Jub. 1:10–11 and 22:16–17, it is argued that the original Hebrew read שׁדים, but that this signified non-existent foreign gods (not demons), as the lexeme does in Psalm 106:37, the text to which both passages allude.
Keywords: Translation; Spirits; Demonology; Jubilees